Answer:
QUESTION?
Step-by-step explanation:
Answer:
A
Step-by-step explanation:
6x-20= 118
6x= 118 + 20
6x = 138
x = 138/6
x= 23
Answer:
13
Step-by-step explanation:
Replace the variable x with -2 in the expression.
f (-2) = -3 x -2 -2
Simplify (-3 x -2 -2) + 9
Multiply -3 by -2
6 - 2 + 9
Subtract 2 from 6
4 + 9
add 4 and 9
13.
Answer:
39.50
42.50
Step-by-step explanation:
Age of the 2 men = sum of the ages of the 6 men - sum of the ages of the 4 men
Average = sum of ages / total number of men
35 = sum of ages / 6
sum of ages = 35 x6 = 210
32 = sum of ages / 4
32 x 4 = sum of ages
128
210 - 128 = 82
age of the younger man = x
age of the older man = 3 + x
x + 3 + x = 82
2x + 3 = 82
2x = 82 - 3
2x = 79
x = 79/2 = 39.5
older man = 39.5 + 3 = 42.50
25÷100=0.25
0.25×680=170 is the answer